(untitled) (Research, Society and Development, 2021)
Given the great energy demand to meet the needs of modern society, it is essential that new alternatives to replace fossil diesel are studied. And biodiesel is an alternative that has been gaining prominence on the world stage, mainly with the use of vegetable oils with a high lipid content, such as Pachira aquatica Aubl, also known as munguba. Given the above, the objective of this work was to extract the oil from the seeds of Pachira aquatica, evaluate the physicochemical characteristics of the oil and define the best conditions for catalytic mixing with temperature variation in the production of biodiesel from the oil obtained. Thus, the acidity index, saponification, refraction, peroxide, water content and fatty acid profile of the oil were evaluated. Fourteen treatments of biodiesel produced with different amounts of sulfuric acid and temperature were evaluated. They were analyzed for water content, specific mass, kinematic viscosity at 40 ºC, refractive index and ester content. It was found that the lipid content of Pachira aquatica seeds was 42.19% and its physical chemistry analysis showed that it can be used in the production of biofuels. There was a greater presence of saturated fatty acids, with a predominance of palmitic acid with 81.95%. Biodiesel produced from oil, on the other hand, showed higher production of esters in relation to the volume used at temperatures of 60 ºC and 0.6 mL of sulfuric acid, and that its properties showed that the plant can be a possible alternative for the production of biodiesel.